Study of hydrogen generation from heavy oil gasification based on ramped temperature oxidation experiments. (19th January 2023) - He, Houfeng; Li, Qiu; Tang, Junshi; Liu, Pengcheng; Zheng, Haoran; Zhao, Fang; Guan, Wenlong; Guo, Erpeng; Xi, Changfeng
Abstract: Hydrogen is a clean energy because of its high energy density and pollution-free combustion. The main ways of hydrogen generation are from coal and methane, as well as hydrogen generation from by-products of chemical plants. It had been reported that heavy oil reservoir in Margaret Lake in Canada produced up to 15 mol% hydrogen indicating that it is feasible to produce hydrogen by in-situ gasification (ISG) from heavy oil reservoir. However, there are relatively few studies on the mechanism and characteristics of hydrogen generation from ISG of heavy oil, the lower limit of hydrogen-production temperature, the interaction of produced gas and so on. Previous studies focused on the upgrading of heavy oil rather than hydrogen generation. In order to study the hydrogen generation mechanisms of different samples, The 4 types samples covering heavy oil, light oil, carbon samples were used and the saturate, aromatic, resin and asphaltene (SARA) components was measured by thin layer chromatography and flame ionization detection (TLC-FID). Then, the ramped temperature oxidation (RTO) experiments of 7 Runs of reservoir cores and sand-filling model were designed. The compositions and molar contents of produced gas were analyzed combined with gas chromatography (GC), and the lower limit temperature and the advantages of hydrogen generation from heavy oil were analyzed under different air/nitrogen injection rates based on a constant water injection rate. The results showed that the lower limit temperature of hydrogen generation from crude oil was about 500–550 °C and that of carbon was 700–750 °C. The reservoir core may had catalytic effect, which can promote hydrogen production. The highest hydrogen rate of RTO experiment with reservoir core can reach 55–60mol%, while that of sand-filling experiment was only 5–10mol%. The main chemical reactions for hydrogen generation from crude oil were coke gasification and water-gas shift. Therefore, the hydrogen production of heavy oil with high hydrocarbon ratio was significantly greater than that of thin oil. It showed the advantages of hydrogen generation from heavy oil. In addition, in order to quantitatively evaluate the efficiency of hydrogen production by gasification, the definition and calculation equation of hydrogen generation efficiency (HGE) were given. The HGE was defined as the ratio of hydrogen production volume and hydrogen consumption volume in a certain period of time (Δt). The E hg can be used to quantitatively represent HGE, and the calculation of E hg is the ratio of hydrogen production and twice of oxygen consumption in a period of time . The E hg of Run1 and Run3 were calculated to be 1.47 and 0.15. It indicated that the hydrogen production efficiency of Run1 was about 10 times higher than that of Run3. Highlights: The experimental method of studying hydrogen generation through RTO experiments was formed. It was confirmed that reservoir cores had advantages of hydrogen generation than sand-filling models. It was confirmed that heavy oil had the advantage of hydrogen generation compared with light oil. The main chemical reactions for hydrogen generation from crude oil were coke gasification and water-gas shift. The concept and equation for quantitative calculation of hydrogen generation efficiency were proposed.